2019
DOI: 10.7567/1347-4065/ab1643
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation for variability characteristics of reflected sound waves from sea surface

Abstract: Many kinds of hydroacoustic devices are used in the field of ocean development of resources and observations. In evaluating the effect of sound propagation in water, it is important to evaluate the characteristics of sound reflection on sea surface. Amplitude and phase of reflected sound waves often fluctuates because of the changing sea surface with waves. In this paper, we evaluated the amplitude and phase variability characteristics of reflected sound waves on sea surface by acoustic simulation with the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The authors have examined the impact of the wave height and wavelength of the sea surface waves on variability characteristics through a model experiment in a wave-making tank and simulation with a finite-difference-time-domain (FDTD) method. 14,15) In this paper, we report on the mechanism of the effect of wave height and wavelength of the wave on the sea surface on variability characteristics of the sea surface reflected wave.…”
Section: Hachiya Et Al Conducted a Model Experiments Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors have examined the impact of the wave height and wavelength of the sea surface waves on variability characteristics through a model experiment in a wave-making tank and simulation with a finite-difference-time-domain (FDTD) method. 14,15) In this paper, we report on the mechanism of the effect of wave height and wavelength of the wave on the sea surface on variability characteristics of the sea surface reflected wave.…”
Section: Hachiya Et Al Conducted a Model Experiments Inmentioning
confidence: 99%
“…Previous studies also showed that the amplitude variability characteristics of the sea surface reflected wave can be described with σ z . [12][13][14] In this study, σ z was calculated using the water level immediately above the sound source for the sea surface in the simulation. Equation (6) shows the relationship between sea surface wavelength Λ and period T observed under the deep-water wave conditions, in which gravitational waves are dominant.…”
Section: Simulation Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The first arrival group recorded up to the delay duration about 50 ms are considered to be multiple arrivals of reflected at bottom and refracted at shallow layer. The second and third arrival groups are sparse arrivals including surface [25][26][27][28] therefore it should be noted that there might be some relation to the wind speed fluctuations. Figure 9 shows a Rx channel mean frequency response of measured CIR and transmission voltage response (TVR) of the transducer used for the element of Tx.…”
Section: Channel Environmentmentioning
confidence: 99%
“…Various numerical methods such as the finite-difference method, 1) the finite element method, 2) and the boundary element method 3) have been proposed for the sound field analysis. In recent years, the finite-difference time-domain (FDTD) method [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] has been widely used because of its simple algorithm and easy programming. This is a tutorial paper focusing on the FDTD method.…”
Section: Introductionmentioning
confidence: 99%